Legal Consequences of Not Fulfilling the Terms of Validity the Agreement between Online Shop Owners and Endorser on Instagram Social Media - Raynaldi Muhammad Saleh (LOCUS MEDIA PUBLISHING, 2022)
Endorsement agreements are developments that occur in society and there are no laws that specifically regulate endorsement agreements. Along with the many needs of endorsement agreements, problems arise such as the non-fulfillment of subjective and objective conditions that cause the endorsement agreement to be canceled. The existence of an agreement, the parties should carry out the agreement in accordance with what has been agreed (consesus), but there are actions that actually violate what has been agreed. The purpose of this research is carried out regarding the unfulfilled conditions of the validity of the agreement between the owner of the online shop and the endorser on Instagram social media. The research method is normative juridical, which is descriptive analysis with literature study data collection techniques. Based on the results of the research, the legal basis for endorsement agreements on Instagram social media according to applicable regulations in Indonesia refers to articles 1313 and 1320 of the Civil Code for the legal side of the agreement and the Law Number 11 Year 2008 on Electronic Information and Transactionsarticle 5 to article 12 for the validity of endorsement agreements made online. The legal consequences of online business cooperation agreement transactions that do not meet the requirements of the validity of the agreement between online shop owners and endorsers on Instagram social media are that online buying and selling transactions are difficult to execute or real action in the event of a dispute or criminal act of fraud. Legal protection for the parties in the endorsement agreement in the event of default by one of the parties can be done by taking litigation or non-litigation.